2017
DOI: 10.2337/db16-1068
|View full text |Cite
|
Sign up to set email alerts
|

Cotransplantation of Mesenchymal Stem Cells With Neonatal Porcine Islets Improve Graft Function in Diabetic Mice

Abstract: Mesenchymal stem cells (MSCs) possess immunoregulatory, anti-inflammatory, and proangiogenic properties and, therefore, have the potential to improve islet engraftment and survival. We assessed the effect human bone marrow-derived MSCs have on neonatal porcine islets (NPIs) in vitro and determined islet engraftment and metabolic outcomes when cotransplanted in a mouse model. NPIs cocultured with MSCs had greater cellular insulin content and increased glucose-stimulated insulin secretion. NPIs were cotransplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 42 publications
3
41
0
Order By: Relevance
“…This raises the possibility of enhancing islet graft functional survival by treating the islets with MSCs before transplantation , so avoiding the logistical, safety, and regulatory concerns of codelivering MSCs in clinical islet transplantation protocols. To date, experimental studies have used a range of different MSCs and in vitro culture conditions , but the effective translation of these experimental observations into improved clinical protocols will require consensus about how best to use MSCs to support graft function. In the current study, we have investigated a number of parameters to optimize the beneficial effects of in vitro coculture of islets with MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This raises the possibility of enhancing islet graft functional survival by treating the islets with MSCs before transplantation , so avoiding the logistical, safety, and regulatory concerns of codelivering MSCs in clinical islet transplantation protocols. To date, experimental studies have used a range of different MSCs and in vitro culture conditions , but the effective translation of these experimental observations into improved clinical protocols will require consensus about how best to use MSCs to support graft function. In the current study, we have investigated a number of parameters to optimize the beneficial effects of in vitro coculture of islets with MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stromal cells (MSCs) offer the potential for improving the outcomes of islet transplantation by exerting anti‐inflammatory, immunosuppressant, and regenerative effects to protect the islet graft . Several studies have demonstrated that cotransplantation of MSCs with islets has beneficial effects on graft function to maintain normoglycemia in animal models of T1D . Some of these effects can be attributed to MSCs influencing the host niche to reduce inflammation , to suppress acquired immune responses , and to enhance graft revascularization .…”
Section: Introductionmentioning
confidence: 99%
“…Studies in rodent models of diabetes have demonstrated that cotransplanting MSCs with islets improves the outcome of islet transplantation in terms of glycemic control . These beneficial effects have been attributed to the ability of MSCs to enhance revascularization or to suppress the host immune responses to the graft .…”
Section: Mscs and Islet Transplantationmentioning
confidence: 99%
“…These beneficial effects have been attributed to the ability of MSCs to enhance revascularization or to suppress the host immune responses to the graft . However, MSCs also improve transplantation outcomes of syngenic grafts , which do not provoke an immune response, and in microencapsulated islet grafts , which do not revascularize, suggesting that MSCs improve graft outomes via multiple mechanisms.…”
Section: Mscs and Islet Transplantationmentioning
confidence: 99%
“…MSCs induce an anti‐inflammatory, immunomodulatory and proangiogenic effect through the secretion of trophic factors such as hepatocyte growth factor (HGF), transforming growth factor β (TGF‐β), vascular endothelial growth factor (VEGF) interleukin‐6 (IL‐6), interleukin‐10 (IL‐10), annexin A1, indoleamine‐2,3‐dioxygenase (IDO), and prostaglandin‐E2 (PGE2) . Our previous study demonstrates that NPI co‐transplanted with bone marrow–derived mesenchymal stem cells (BMSCs) induce the rapid graft vascularization and thereby enhances the graft function . Therefore, these cells may have the potential to stimulate rapid graft vascularization and modulate the immune microenviroment within the DL subcutaneous space and thereby enhancing the function of co‐transplanted islets.…”
Section: Introductionmentioning
confidence: 99%